Quantitation of Replication-Competent HIV-1 in Populations of Resting CD4(+) T Cells - Soriano-Sarabia, Natalia (J Virol, 2014)
Central memory (T(CM)) CD4(+) T cells are the principal reservoir of latent HIV-1 infection that persists despite durable, successful antiretroviral therapy (ART). In a study that measured HIV DNA in 17 patients and replication-competent HIV in 4 patients, pools of resting and activated transitional memory (T(TM)) CD4(+) T cells were found to be a reservoir for HIV infection. As defective viruses account for the majority of integrated HIV DNA and do not reflect the actual frequency of latent, replication-competent proviral infection, we assessed the specific contribution of resting T(TM) cells to latent HIV infection. We measured the frequency of replication-competent HIV in purified resting memory cell subpopulations by a limiting-dilution, quantitative viral outgrowth assay (QVOA). HIV was routinely detected within the resting central memory compartment but was infrequently detected within the resting T(TM) compartment. These observations suggest that prolonged ART may limit persistent latent infection in the T(TM) compartment. Our results confirm the importance of latent infection within the T(CM) compartment and again focus attention on these cells as the most important latent viral reservoir. While proliferation may drive expansion of detectable viral genomes in cells, the frequency of replication-competent HIV must be carefully assessed. Latent infection appears to wane within the transitional memory compartment in patients who have sustained successful viral suppression via ART or were treated very early in infection. IMPORTANCE Antiretroviral therapy (ART) has led to a significant decrease in morbidity and mortality among HIV-infected patients. However, HIV integrates into the genome of CD4(+) T cells, generating pools of long-lived cells that are reservoirs of latent HIV. Two main subsets of CD4(+) T cells, central memory and transitional memory cells, were reported to be major reservoirs of HIV infection. However, this study primarily measured the HIV DNA content, which also includes defective proviruses that would not be able to replicate and initiate new rounds of infection. By analyzing the replication-competent virus in both cell subsets, we showed that transitional memory cells may not be a durable reservoir in patients on successful ART.